Wpływ "Vita Martini" Sulpicjusza Sewera na Vita Niniani Aelreda z Rievaulx - Groń, Ryszard (Vox Patrum, 2014)
The article was written to illustrate the possible impact of Vita Martini by Sulpicius Severus on Aelred of Rievaulx’s Vita Niniani. Both works are hagiographies, thus were written as prime examples of faith and Christian virtues without excessive focus on biographical accuracy, as was common during the medieval period. The works were created in diverse cultural and historical settings: the former portrays the life of Saint Martin of Tours, a very popular medieval bishop of Gaul, who was active during the 5th century; the hagiography was written by his disciple, Sulpicius Severus. The latter depicts the life of a missionary active in southern England, also in the 5th century, Saint Ninian of Whithorn. St. Ninian’s hagiography was, however, written seven centuries later by a well-known English abbot from Rievaulx, St. Aelred. The possible influence of Sulpicius Severus’ work on Vita Niniani by Aelred of Rievaulx can be concluded due to the similarities between the two hagiographies, the popularity of Vita Martini in Cistercian circles and, simultaneously, an almost complete lack of historical information regarding St. Ninian’s life. The fact that Aelred quotes the Bede Venerable’ history note from the 8th century – which mentions that St. Martin was St. Ninian’s role model in the field of missionary care and pastoral work – as his chief resource, makes this influence is all the more probable. To carry out this article’s objective, the contents have been divided into three sections: the creation of Vita Niniani; a comparison of Bishop Ninian of Whithorn as a historical figure (based on contemporary historical and archeological research) with the portrait painted by Aelred (based on the Bede Venerable’ note and a piece of literature by an unknown writer); to finally show a comparison of Vita Niniani and Vita Martini.